Investigation and cause analysis of out-patient experience based on brand recognition model (基于品牌认知模型的门诊就诊患者体验调查与原因分析) - WAN Meifeng (万美凤); ZHU Hengmei (朱恒美); FANG Shuheng (房树恒); ZHANG Yanli (张延丽) (中西医结合护理)
Objective By studying the relationship between outpatient experience and satisfaction, loyalty, and recommendation, find out the current factors affecting the medical experience of outpatient, and improve the overall service quality of the hospital. Methods Using indicators of Outpatient Experience Questionnaire (OPEQ), Patient Experience With Medical care (PEES-50) and other questionnaires, a model of the relationship between patient experience and satisfaction, loyalty, and recommendation was built, and expected satisfaction degree was considered as an intermediary variable to study the interaction between model variables. Results Outpatient experience directly affected their satisfaction and recommendation for hospital services, and indirectly affects satisfaction, loyalty and recommendation through expectation satisfaction. Conclusion The key to improving patient experience lies in improving the quality of hospital services and management, and providing quantitative support for improving the quality of hospital services. (目的 研究门诊患者体验感与满意度、忠诚度、推荐度之间的关系, 找出当前影响门诊患者就诊体验的因素, 提升医院整体的服务质量。方法 便利选取300名门诊就诊患者, 采用门诊患者体验量表(OPEQ)、患者体验医疗服务质量评价表(PEES-50)等问卷指标, 对患者体验感与满意度、忠诚度、推荐度之间的关系构建模型, 并加入中介变量期望满足度, 以确定变量之间的影响作用。结果 门诊患者体验感直接影响其对医院服务的满意度与推荐度, 还通过期望满足度间接影响满意度、忠诚度与推荐度。结论 提高患者的体验感关键在于提高医院的服务与管理质量, 为提升医院服务质量提供量化支撑。)